“Reward comes, when you are not there”. The image of Catholicism and Buddhism in the TV series Siła wyższa [Higher Power] by Wojciech Adamczyk - Demby, Łucja (Studia religiologica, 2018)
The paper by Łucja Demby discusses the television series Siła wyższa [Higher Power], first broadcast on Polish TVP1 public television in 2012. The series was directed by Wojciech Adamczyk, familiar to viewers as the creator of the extremely popular TV series Ranczo [The Ranch]. Higher Power, in a comedic convention, depicts the confrontation between Franciscan monks and the residents of a nearby Buddhist centre. Łucja Demby points to Wojciech Adamczyk’s trademarks present in the series (notable also in The Ranch and the director’s other work), such as including a message of tolerance and understanding between people of different persuasions. The author also points out how the series draws on religious stereotypes functioning in Polish society, concerning both the dominating Catholicism and other religions. In terms of composition, the paper is based around two quotes: a statement by Lama Rinchen regarding the possibility of dialogue between Catholicism and Buddhism, and a fragment from a book by Pope John Paul II, emphasizing the differences between these two religions.